(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2021)
The mangrove ecosystem in Subang Coastal is potentially effected due to oil spills. The oil spill in this area can be caused by an accident of petroleum exploitation. Therefore, it needs to anticipate and plan comprehensively for environmental protection from oil spills. Environmental sensitivity index (ESI) analysis can be used to classify the level of sensitivity of the mangrove ecosystem to the oil spill. This study aims to calculate the ESI for mangrove ecosystems in Subang coastal areas. ESI was formed by combining the Vulnerability Index (VI), Ecological Index (EI), and Socio-economic Index (SI). Secondary data was collected by study literature. The primary data was conducted from 13 locations. The parameters in VI are coastal slope, tidal type, tidal range, wave height, substrate type, and mangrove distance from the coastline. The parameters in EI are mangrove zonation, mangrove density mangrove diversity, age of mangrove, protected species, and mangrove conservation status. The parameter in SI consists of social and economic components. The result showed that the mangrove ecosystem of the Subang coastal area has a sensitivity status from moderate to sensitive. Among 13 locations, only three locations were classification sensitive to the oil spill. The locations were Tegal Tike, Anggaranu, and Tanjung. Although the study areas are dominated by the moderate sensitivity category, however, the protection of the mangrove ecosystem from oil spills should be prioritized.